2007
DOI: 10.1038/sj.bjc.6603774
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and humoral mechanisms of osteoclast formation in Ewing's sarcoma

Abstract: Cellular mechanisms that account for tumour osteolysis associated with Ewing's sarcoma are uncertain. Osteoclasts are marrowderived multinucleated cells (MNCs) that effect tumour osteolysis. Osteoclasts are known to form from macrophages by both receptor activator for nuclear factor-kB (RANK) ligand (RANKL)-dependent and -independent mechanisms. In this study, our aim has been to determine whether tumour-associated macrophages (TAMs) isolated from Ewing's sarcoma are capable of differentiating into osteoclasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 35 publications
(45 reference statements)
1
29
0
Order By: Relevance
“…Because osteosarcoma and ES cells are metabolically active bone cells (17,18), studies with bisphosphonates and more specifically nitrogen-containing bisphosphonates have shown selective uptake and "poisoning" of these cells (19)(20)(21)(22)(23). We have previously shown that zoledronic acid is able to limit tumor progression in a rat model of osteosarcoma, to prevent tumor relapse compared with chemotherapy alone and to prevent osteolytic lesions (10).…”
Section: Discussionmentioning
confidence: 99%
“…Because osteosarcoma and ES cells are metabolically active bone cells (17,18), studies with bisphosphonates and more specifically nitrogen-containing bisphosphonates have shown selective uptake and "poisoning" of these cells (19)(20)(21)(22)(23). We have previously shown that zoledronic acid is able to limit tumor progression in a rat model of osteosarcoma, to prevent tumor relapse compared with chemotherapy alone and to prevent osteolytic lesions (10).…”
Section: Discussionmentioning
confidence: 99%
“…Single-strand complementary DNA (cDNA) was synthesized from 2.0 µg of total RNA using the SuperScript® First-Strand Synthesis System for semiquantitative reverse transcription polymerase chain reaction (RT-PCR; Invitrogen, Paisley, UK). cDNA was amplified by PCR using specific primers to RANKL, OPG, and TRAIL with GAPDH control as previously described [24,25]. PCR products were fractionated on 1% agarose gels, and gel pictures were scanned with Alpha-Imager 2200 (Alpha Innotech Corporation, USA).…”
Section: Leiomyosarcoma-monocyte Cocultures and Messenger Rna Expressmentioning
confidence: 99%
“…This finding suggests that osteolysis in adamantinoma of long bones and osteofibrous dysplasia most likely occurs by RANKL-expressing mesenchymal stromal cells inducing macrophages in osteofibrous dysplasia and adamantinoma of long bones to undergo osteoclast differentiation, as occurs in other primary bone tumours. 15,28,29 There are close similarities in tumour location and radiological features between osteofibrous dysplasia and adamantinoma of long bones. Our findings show that there are similarities and differences in stromal cell expression of epithelial and osteoblast markers in these lesions.…”
Section: Discussionmentioning
confidence: 98%